Effect of Al2O3 and CaF2 additives on the viscosity of conventional cryolite melts - A. S. Lyutina; A. A. Kataev; A. V. Rudenko; O. Yu. Tkacheva (Chimica Techno Acta)
The viscosity of cryolite melts of conventional composition NaF–AlF3–CaF2–Al2O3 was studied by rotational viscometry using the FRS 1600 high-temperature rheometer. The cryolite ratio of the NaF–AlF3 melt was 2.1, 2.3, and 2.5; the Al2O3 content varied from 2 to 6.6, and CaF2 – from 0 to 8 wt%. The measurements were carried out in the temperature range from liquidus to 1200 °C. The conditions for the laminar flow of the investigated melts were determined, based on the measurements of the cryolite melts viscosity as a function of the shear rate at a constant temperature. A shear rate of 12 ± 1 s–1 was chosen for studying the viscosity temperature dependence for all samples. The viscosity temperature dependence of cryolite melts is described by a linear equation. The temperature coefficient b in this equation has negative values and varies in the range of (–0.01)–(–0.06) mPa·s/deg. It was found that the viscosity of cryolite melts of conventional composition in the range of operating temperatures of aluminum electrolysis (950–970 °C) varies from 2.5 to 3.7 mPa·s (depending on the composition and temperature). The viscosity of cryolite-alumina melts increases with the rise of alumina content: 1 wt% Al2O3 increases the viscosity, on average, by 1%. However, the influence of CaF2 is more significant: the addition of 1 wt% CaF2 leads to an increase in viscosity by 3%. A decrease in the CR of the melt by 0.1 (in the range of 2.1–2.5) leads to a decrease in the viscosity of cryolite melts by 2.3%. A viscosity regression equation for the cryolite melts of conventional composition as a function of several independent parameters (temperature, CR, CaF2 and Al2O3 content) is obtained by the multivariable approximation of experimental data. The equation satisfactorily (within 1.5%) describes the viscosity of conventional industrial electrolytes and can be used for estimation of their viscosity.